Assessing the Innovation Attractiveness of Areas: Problems and Solutions - NECHAEV, Andrey S.; ANTIPINA, Oksana V. (Journal of Advanced Research in Law and Economics, 2016)
The effectiveness of comprehensive development programs largely depends on the qualitative assessment of innovative foundation of areas. Particular attention in stimulating innovative activities should be paid to the application of various tax instruments, which influence the tax burden for businesses. Thus, the study offers a developed algorithm for enhancing innovation attractiveness of administrative-territorial units. The model includes the fiscal component that provides the possibility to comprehensively estimate the potential of areas (federal districts, territorial entities of the Russian Federation) in conjunction with and in terms of interrelation with tax burden parameters, thus providing the improved innovative development of areas. Besides, the study demonstrates assessment results of innovation attractiveness of the Russian federal districts and regions. They include the calculation of deviations from the specified values and targets for each indicator of innovative development, including the fiscal component that enhances management effectiveness of the innovative development and control over the administrative-territorial units.